Post-Offer Employment Testing and Its Impact on Health Care Costs for Employers. Issue 2 (17th February 2023) - Hoffman, Ben; Schaneman, Justin
Abstract : Injury prevention and management is a major workplace and public health imperative. Post-offer employment tests are an excellent tool to prevent workplace injuries and to reduce overall health related expenditures including group health, medical related absences, pharmaceutical plan costs, motor vehicle crashes related to health conditions and employee turnover. Abstract : Objective: To quantify the cost benefits associated with Post-Offer Employment Testing (POET). Methods: Cross-sectional analysis of 5 million individuals/480 million medical, prescription, absence, short- and long-term disability, property and casualty and workers' compensation claims. Individuals who received POET were statistically matched by company, position, age, and gender to candidates who did not. Results: Significant injury reduction rates and integrated benefits cost savings were found in the cohort screened by POET. Conclusion: POET is an effective tool for the employer to manage health, disability, motor vehicle crash, at-work injury costs, and reduce turnover.